Music in Goethe's Faust : Goethe's Faust in music - Bodley, Lorraine Byrne, 1968- (The Boydell Press, 2017)
That Goethe's poetry has proved pivotal for the development of the nineteenth-century Lied has long been acknowledged. Less acknowledged is the seminal impact in musical realms of Goethe's Faust/I>, a work which has attracted the attention of composers since the late eighteenth century and played a vital role in the evolution of vocal, operatic and instrumental repertoire in the nineteenth century.